Causalidad y operaciones en la interpretación de las concepciones espontáneas - Pacca, Jesuïna Lopes de Almeida; Saraiva, J. A. F. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This work analyses aspects of Piagees genetic epistemology concerning the construction of the notion of causality which, although being developed in parallel with the operatory notions, cannot be identified with them. Such differentiation is important to understand the knowledge of students shown trough spontaneous conceptions. The idea of necessity, which in Piaget's theory, is essential for the construction of causal relations, is considered here as a relative necessity, making sense and having value when referred to a system of explanation. Considering alternative conceptions as models of explanation of physical phenomena, the relations in these models must be causal and necessary in respect to a physical system, incomplete and inadequate as it might be.